Trust based Lightweight Security Protocol for Device to Device Multihop Cellular Communication - Yasir, Javed (Universiti Malaysia Sarawak (UNIMAS), 2020)
Device to Device (D2D) communication has gained a lot of popularity in recent years as it offers high speed, extended coverage, and ubiquitous connectivity. It is one of the key approaches that has revolutionized communication and is the basis of the 5G network. D2D allows small devices such as mobile phones, tablets to act as Non-transparent relays (NTR) where they can provide services as well as forward traffic, request or services besides basic function that is direct communication without the need of Base Station (BS). This concept of multihop D2D communication has introduced a number of issues that were non-prevalent in current cellular communication. The major issue is security that is allowing D2D communication in a secure and trustworthy manner. Another issue, that is challenging is that current proven used security approaches cannot be adapted as devices that require security have limited computation and space as well as they are constrained by power and bandwidth issues. NTR arise another issue that is trust, that means how these devices can be trusted as well as how the identity of users can be protected. In order to handle these issues, a trustworthy lightweight security scheme that allows multihop secure communication is designed that is called as Trust Based Lightweight Security Protocol in multihop D2D communication (TLwS). Formal and computational analysis of TLwS shows that it can mitigate replay attack, Man-in-the-Middle (MITM) attack, freshness attack, interleaving attack, and masquerading attack. It also achieves confidentiality, integrity and avoids any no-repudiation attack. The computational overhead shows that TLwS is at least 40% better than popular algorithm such as SeDS, UAKA-D2D, and D2D-Assist. Discrete logarithm analysis shows that TLwS is secure against the current security algorithms as well as quantum attacks. TLwS offers flexibility that allows it to be used in any kind of security environment. Processing time for TLwS is at least 50% better than benchmarking schemes. TLwS can be used easily in 5G communication where it will allow multihop D2D secure communication.